Formation of skills and abilities of a specialist in the technical field - Stukalska (Ivanova), Nataliia; Kuzmin, Oleg (My University, 2021)
The aim of the work is to substantiate the expediency of using various teaching methods to formulate the skills and abilities of a specialist in the field of food technologies. Мета роботи – обґрунтувати доцільність використання різноманітних методів навчання для формування умінь і навичок фахівця в галузі харчових технологій.
Keywords: кафедра технології ресторанної і аюрведичної продукції; technical field; food technology; teaching methods; технічна галузь; харчові технології; методи навчання